2017
DOI: 10.1128/msphere.00375-16
|View full text |Cite
|
Sign up to set email alerts
|

Host Range Restriction of Insect-Specific Flaviviruses Occurs at Several Levels of the Viral Life Cycle

Abstract: Most viruses of the genus Flavivirus, e.g., YFV and dengue virus, are mosquito borne and transmitted to vertebrates during blood feeding of mosquitoes. Within the last decade, an increasing number of viruses with a host range exclusively restricted to insects in close relationship to the vertebrate-pathogenic flaviviruses were discovered in mosquitoes. To identify barriers that could block the arboviral vertebrate tropism, we set out to identify the steps at which the ISF replication cycle fails in vertebrates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
53
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(60 citation statements)
references
References 49 publications
2
53
0
Order By: Relevance
“…Each of these steps is an obstacle to be overcome by the virus [ 32 ]. To study the mechanisms behind host-range restrictions reverse genetic systems have proven to be a valuable tool through the ability of creating chimeric viruses [ 28 , 31 , 33 ].…”
Section: Host-range Restrictions Of Isvsmentioning
confidence: 99%
See 1 more Smart Citation
“…Each of these steps is an obstacle to be overcome by the virus [ 32 ]. To study the mechanisms behind host-range restrictions reverse genetic systems have proven to be a valuable tool through the ability of creating chimeric viruses [ 28 , 31 , 33 ].…”
Section: Host-range Restrictions Of Isvsmentioning
confidence: 99%
“…A study by Junglen et al [ 33 ] also showed that the host-range restriction can be at several levels of the viral life cycle. In this study chimera Yellow fever virus carrying envelope proteins from the insect-specific flavivirus Niénokoué virus (NIEV) was use to study host range restrictions.…”
Section: Host-range Restrictions Of Isvsmentioning
confidence: 99%
“…WNV mutants lacking production of sfRNA1, or sfRNA1 and sfRNA2 were shown to exhibit reduced pathogenicity in mice (Pijlman et al, 2008). Later studies demonstrated the pivotal role of sfRNA in replication, dissemination and transmission of a wide range of flaviviruses (Chang et al, 2013;Donald et al, 2016;Filomatori et al, 2017;Junglen et al, 2017).…”
Section: Functions Of Sfrnamentioning
confidence: 99%
“…All together, the current studies highlight gaps in the understanding of interactions between ISVs and other pathogenic viruses. It has been shown that the host range restriction of insect-specific flaviviruses and alphaviruses occurs at different levels of viral replication cycle (Nasar et al, 2015;Junglen et al, 2017). Among intrinsic and extrinsic factors affecting viral replication and transmissibility, temperature was shown to be of an extreme importance (Samuel et al, 2016).…”
Section: Discussionmentioning
confidence: 99%